Respuesta :

2y + 5 = 3y + 2

=> 5 - 2 = 3y - 2y

= 3 = y

Answer:

y = 3

Step-by-step explanation:

2y + 5 = 3y + 2

2y - 3y + 5 = 3y - 3 y + 2                  [ subtract both sides by 3y ]

- y + 5 = 0 + 2                                  [ 3y - 3y = 0 ]

- y + 5 - 5 = 2 - 5                              [ subtract by 5 on  both sides ]

- y + 0 = - 3                                      [ -5 + 5 = 0 ]

  - y = - 3                      

     y = 3                                          [ divide by - 1 on both sides ]